The Basic Psychological Needs in the Classroom Scale (BPN-CS) - Pedro Javier Conesa; Jon Andoni Duñabeitia (Behavioral Sciences, 2021)
Recent experimental and theoretical studies have shown that the assessment of students’ satisfaction of their basic psychological needs (BPN) can be a powerful resource to identify different areas to improve their well-being, engagement, or learning achievement in school contexts. However, currently, the number of validated tools to assess the satisfaction of the BPN is very low, hindering informed decision-making strategies at the educational level. The aim of this study was to develop and validate the Basic Psychological Needs in the Classroom Scale (BPN-CS) instrument, adapting existing instruments and putting the new tool to the test. The BPN-CS was developed to measure the level of satisfaction of autonomy, competence, relatedness, and novelty in the classroom. We tested the scale on a representative sample of 1344 Spanish elementary school students from 8 to 13 years old. A series of analyses were run in order to test the internal consistency of the main factors as well as to prove the convergent and divergent validity of the instrument. In summary, the BPN-CS is presented as a reliable and valid self-report instrument to measure basic psychological needs in a classroom context with elementary school pupils in the Spanish context.